Білоруська етнологія в XXI столітті: проблеми і перспективи - Гурко, О. (Народна творчість та етнографія, 2009)
In 1990s the Institute of Art Criticism, Ethnography and Folklore of K. Krapivy of NАS of Belarus began researches in ethnology area. The beginning of the ХХІ century has put a number of the important problems, which had not just a theoretical, but also an applied value. Among the major problems – definition of a role and value of ethnic traditions in development of modern Belarus culture; revealing of ethnocultural features of the Belarus regions and popularization of an ethnocultural legacy for tourist activity; monitoring ethnic and religions processes; learning of mechanisms of ethnic adaptation of migrants in Belarus; creating of the system of modern ethnologic terminology, and a number of other problems which are studied at the present stage. Ethnology has passed in Belarus a stage of the formation, and now it is possible to talk about the beginning of a stage of its development.